Optical adhesive sheet and release liner-attached optical adhesive sheet

By developing an optical adhesive with a maximum height of Sz of 500nm or below and haze meets specific conditions when stretched at 150% , the uneven defects and haze problems of optical adhesive surface in flexible equipment are solved, ensuring the display effect of the display screen.

JP2025063492APending Publication Date: 2025-04-16NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172743
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

During the deformation of flexible equipment, the surface uneven defects and haze problems of existing optical adhesives are more prominent, affecting the display effect of the display screen.

Method used

An optical adhesive is developed with the first and second bonding surfaces at a maximum height Sz of 500 nm or below and the haze at 150% stretching satisfies certain conditions to ensure that the haze is maintained in both non-stretched and stretched states.

Benefits of technology

By controlling the surface flatness and haze of the optical adhesive, the surface uneven defects and haze increase during deformation of the flexible equipment are effectively suppressed, ensuring the display effect of the display screen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063492000001_ABST
    Figure 2025063492000001_ABST
Patent Text Reader

Abstract

To provide an optical adhesive sheet suitable for use in flexible device applications, and a release liner-attached optical adhesive sheet.SOLUTION: An adhesive sheet 10 according to the present invention is an optical adhesive sheet having an adhesive surface 11 and an adhesive surface 12 on the opposite side from the adhesive surface 11. The maximum height Sz of the adhesive surfaces 11, 12 is 500 nm or less. The haze H150% at 150% elongation and the haze H0% at non-elongation of the adhesive sheet 10 satisfy |H150-H0|≤1.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical pressure-sensitive adhesive sheet and an optical pressure-sensitive adhesive sheet with a release liner. [Background technology]

[0002] A display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover film. In the manufacturing process of such a display panel, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure. The optical adhesive sheet is manufactured in the form of an adhesive sheet with a release liner, in which both sides of the sheet are covered with a release liner.

[0003] Meanwhile, the development of stretchable display panels for tablet terminals, for example, is progressing. A stretchable display panel is a display panel that can be repeatedly deformed (stretched, twisted, folded, etc.). In a stretchable display panel, each element in a laminated structure is manufactured so as to be repeatedly deformable. A thin optical adhesive sheet is used for bonding between such elements. An optical adhesive sheet for flexible devices such as a stretchable display panel is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-111754 A Summary of the Invention [Problem to be solved by the invention]

[0005] Optical adhesive sheets for display panels are required to have small defects caused by unevenness on the adhesive sheet surface (surface unevenness defects) so that they do not affect the display image of the display panel. However, in deformed areas of optical adhesive sheets for flexible devices, the surface unevenness defects are stretched and enlarged due to the deformation. Therefore, optical adhesive sheets for flexible devices are required to have even smaller surface unevenness defects than conventional optical adhesive sheets for display panels.

[0006] In addition, optical adhesive sheets for display panels are required to have low haze so as not to affect the image displayed on the display panel. Optical adhesive sheets for flexible devices are required to have low haze both in the undeformed and deformed states. However, even if a conventional optical adhesive sheet is transparent when left at rest (in a natural length without deformation), depending on the monomer composition of the polymer components (polymers, oligomers) in the adhesive sheet and the compatibility between the polymer components and additives (low molecular weight components), the additives and other components may aggregate in the deformed state, causing an increase in haze.

[0007] The present invention provides an optical adhesive sheet and an optical adhesive sheet with a release liner that are suitable for flexible device applications. [Means for solving the problem]

[0008] The present invention [1] is an optical adhesive sheet having a first adhesive surface and a second adhesive surface opposite to the first adhesive surface, wherein the maximum height Sz of the first adhesive surface and the second adhesive surface is 500 nm or less, and the haze H at 150% elongation is 150 (%) and the haze H0 (%) when unstretched are |H 150 Includes optical adhesive sheets that satisfy -H0|≦1.0.

[0009] The present invention [2] includes the optical adhesive sheet according to the above [1], in which the haze H0 is 2.0% or less.

[0010] The present invention [3] includes the optical adhesive sheet according to the above [1] or [2], which has a yield strain Y1 of 150% or more in a first tensile test at 23°C and a tensile speed of 10 mm / min.

[0011] The present invention [4] includes an optical adhesive sheet according to any one of [1] to [3] above, in which the yield strain Y2 in the second tensile test under conditions of 23°C and a tensile speed of 1500 mm / min is 150% or more.

[0012] The present invention [5] has a strain stress S1 after the first third tensile test under the conditions of 23° C., a tensile speed of 200 mm / min, and an elongation length of 150%, and has a strain stress S 10 and the stress S 10 The optical adhesive sheet according to any one of [1] to [4] above, wherein the ratio of is 0.5 or more.

[0013] The present invention [6] provides an optical adhesive sheet with a release liner, comprising the optical adhesive sheet described in any one of [1] to [5] above, a first release liner releasably contacting the first adhesive surface, and a second release liner releasably contacting the second adhesive surface.

[0014] The present invention [7] includes an optical adhesive sheet with release liner as described in [6] above, in which the maximum height Sz of the surface of the first release liner facing the optical adhesive sheet is 2000 nm or less, and the maximum height Sz of the surface of the second release liner facing the optical adhesive sheet is 2000 nm or less. Effect of the Invention

[0015] As described above, the optical adhesive sheet of the present invention has a maximum height Sz of 500 nm or less on the first adhesive surface and the second adhesive surface. The adhesive surface of the optical adhesive sheet in the flexible device has a high smoothness of a maximum height Sz of 500 nm or less, which is suitable for suppressing the occurrence of large surface irregularity defects not only in the non-deformed parts of the adhesive sheet but also in the deformed parts. In addition, as described above, the optical adhesive sheet has a haze H at 150% elongation. 150 (%) and the haze H0 (%) when unstretched are |H 150 -H0|≦1.0 is satisfied. This is suitable for suppressing an increase in haze in the deformed portion of the optical adhesive sheet when the flexible device including the optical adhesive sheet is deformed. Therefore, the optical adhesive sheet is suitable for suppressing the occurrence of large surface irregularity defects and suppressing an increase in haze. Such an optical adhesive sheet is suitable for flexible device applications.

[0016] The optical adhesive sheet with release liner of the present invention comprises the optical adhesive sheet as described above, and is therefore suitable for flexible device applications as a supply material for the optical adhesive sheet. [Brief description of the drawings]

[0017] [Figure 1] 1 is a schematic cross-sectional view of an optical adhesive sheet with a release liner according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] As shown in FIG. 1, an adhesive sheet 10 as one embodiment of the optical adhesive sheet of the present invention has a sheet shape of a predetermined thickness and extends in a direction (plane direction) perpendicular to the thickness direction. The adhesive sheet 10 has an adhesive surface 11 (first adhesive surface) and an adhesive surface 12 (second adhesive surface) opposite to the adhesive surface 11. FIG. 1 shows a state in which release liners 20, 30 are attached to the adhesive surfaces 11, 12 of the adhesive sheet 10. The release liner 20 is disposed on the adhesive surface 11. The release liner 30 is disposed on the adhesive surface 12. That is, the adhesive sheet X with release liner shown in FIG. 1 includes the release liner 20, the adhesive sheet 10, and the release liner 30 in this order in the thickness direction H. The adhesive sheet X with release liner is one embodiment of the optical adhesive sheet with release liner of the present invention.

[0019] The adhesive sheet 10 has a maximum height Sz of 500 nm or less on the adhesive surfaces 11 and 12, and a haze H 150 (%) and the haze H0 (%) when unstretched are |H 150 -H0|≦1.0 is satisfied. The maximum height Sz is a parameter related to the surface properties based on ISO 25178-2:2012. The method for measuring the maximum height Sz is as described below in the examples. The haze H0 is the haze when the pressure-sensitive adhesive sheet 10 is not deformed, such as stretched. Haze H 150 is the haze when the adhesive sheet 10 is stretched in one direction by 150% of its length. 150 The method for measuring is as described below in the Examples.

[0020] As described above, the adhesive sheet 10 has a maximum height Sz of 500 nm or less on the adhesive surfaces 11 and 12. Having high smoothness with a maximum height Sz of 500 nm or less on the adhesive surfaces 11 and 12 of the adhesive sheet 10 in a flexible device is suitable for suppressing the occurrence of large surface irregularity defects not only in the non-deformed parts of the adhesive sheet 10 but also in the deformed parts. The present inventors have found that the maximum height Sz is useful as an index for suppressing surface irregularity defects in the adhesive sheet 10 for flexible devices. The present invention is based on such findings.

[0021] In addition, as described above, the adhesive sheet 10 has a haze H 150 (%) and the haze H0 (%) when unstretched are |H 150 −H0|≦1.0 is satisfied. This is suitable for suppressing an increase in haze in the deformed portion of the adhesive sheet 10 when a flexible device including the adhesive sheet 10 is deformed.

[0022] Therefore, the pressure-sensitive adhesive sheet 10 is suitable for suppressing the occurrence of large surface irregularity defects and suppressing an increase in haze. Such a pressure-sensitive adhesive sheet 10 is suitable for flexible device applications.

[0023] The adhesive sheet X with release liner includes the adhesive sheet 10 as described above, and is therefore suitable for flexible device applications as a supply material for optical adhesive sheets.

[0024] The maximum height Sz of the pressure-sensitive adhesive sheet 10 is preferably 400 nm or less, more preferably 300 nm or less, from the viewpoint of suppressing the above-mentioned surface irregularity defects. The maximum height Sz of the pressure-sensitive adhesive sheet 10 is preferably 50 nm or more, more preferably 100 nm or more, and even more preferably 150 nm or more, from the viewpoint of preventing blocking in the roll-shaped pressure-sensitive adhesive sheet 10. That is, the maximum height Sz of the pressure-sensitive adhesive sheet 10 is preferably 50 to 500 nm, more preferably 100 to 400 nm, and even more preferably 150 to 300 nm, from the viewpoint of both suppressing the above-mentioned surface irregularity defects and preventing the above-mentioned blocking. Examples of methods for adjusting the maximum height Sz of the pressure-sensitive adhesive sheet 10 include adjustment of the surface roughness, such as the maximum height Sz, of the release surfaces 21, 31 (contacting the pressure-sensitive adhesive sheet 10) of the release liners 20, 30. Examples of methods for adjusting the surface roughness of the release surfaces 21, 31 include adjustment of the surface roughness of the coating film when a release treatment agent is applied to the liner substrate described below.

[0025] From the viewpoint of ensuring the transparency required for the pressure-sensitive adhesive sheet 10, the haze H0 of the pressure-sensitive adhesive sheet 10 is preferably 2.0% or less, more preferably 1.0% or less, even more preferably 0.5% or less, and even more preferably 0.25% or less. The haze H0 of the pressure-sensitive adhesive sheet 10 is, for example, 0.0% or more. That is, from the viewpoint of ensuring the transparency required for the pressure-sensitive adhesive sheet 10, the haze H0 of the pressure-sensitive adhesive sheet 10 is preferably 0.0 to 2.0%, more preferably 0.0 to 1.0%, even more preferably 0.0 to 0.5%, and even more preferably 0.0 to 0.25%. The haze H0 of the pressure-sensitive adhesive sheet 10 can be measured using a haze meter in accordance with JIS K7136:2000 (haze H 150The same applies to (1) and (2). Examples of haze meters include "NDH2000" manufactured by Nippon Denshoku Industries Co., Ltd. and "HM-150N" manufactured by Murakami Color Research Laboratory Co., Ltd. Specific methods for measuring haze H0 are as described below in relation to the Examples. Methods for adjusting haze H0 include, for example, selecting the type of base polymer in pressure-sensitive adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount. Methods for adjusting haze H0 include, for example, selecting the type of components other than the base polymer in pressure-sensitive adhesive sheet 10, adjusting the molecular weight, and adjusting the blending amount. These adjustment methods are effective in reducing haze H 150 The same applies to.

[0026] Adhesive sheet 10 Haze H 150 From the viewpoint of ensuring the required transparency of the pressure-sensitive adhesive sheet 10 when stretched, the haze H of the pressure-sensitive adhesive sheet 10 is preferably 2.0% or less, more preferably 1.0% or less, even more preferably 0.5% or less, and even more preferably 0.25% or less. 150 is, for example, 0.0% or more. That is, the haze H 150 From the viewpoint of ensuring the required transparency when the pressure-sensitive adhesive sheet 10 is stretched, the haze H is preferably 0.0 to 2.0%, more preferably 0.0 to 1.0%, even more preferably 0.0 to 0.5%, and even more preferably 0.0 to 0.25%. 150 The specific method for measuring is as described below in the Examples.

[0027] The pressure-sensitive adhesive sheet 10 has a yield strain Y1 in a first tensile test under conditions of 23° C. and a tensile speed of 10 mm / min. The method of the first tensile test is specifically as described below in relation to the Examples. The yield strain Y1 is preferably 150% or more, more preferably 160% or more, and even more preferably 170% or more, from the viewpoint of ensuring the flexibility of the pressure-sensitive adhesive sheet 10 to follow the deformation of the adherend in the low speed range. The yield strain Y1 is preferably 200% or less, more preferably 190% or less, and even more preferably 180% or less, from the viewpoint of ensuring the restorability (shape restorability) when the pressure-sensitive adhesive sheet 10 returns to its original shape after being stretched. The yield strain Y1 is preferably 150 to 200%, more preferably 160 to 190%, and even more preferably 170 to 180%, from the viewpoint of achieving both the above-mentioned flexibility and the above-mentioned shape restorability. The method of adjusting the yield strain Y1 includes, for example, selecting the type of components constituting the pressure-sensitive adhesive sheet 10 and adjusting the blending amount.

[0028] The pressure-sensitive adhesive sheet 10 has a yield strain Y2 in a second tensile test under conditions of 23° C. and a tensile speed of 1500 mm / min. The method of the second tensile test is specifically as described below with reference to the Examples. The yield strain Y2 is preferably 150% or more, more preferably 170% or more, and even more preferably 180% or more, from the viewpoint of ensuring the flexibility of the pressure-sensitive adhesive sheet 10 to follow the deformation of the adherend in the high-speed range. The yield strain Y2 is preferably 220% or less, more preferably 210% or less, and even more preferably 200% or less, from the viewpoint of ensuring the shape restoring property after the pressure-sensitive adhesive sheet 10 is stretched. The yield strain Y2 is preferably 150 to 220%, more preferably 170 to 210%, and even more preferably 180 to 200%, from the viewpoint of achieving both the above-mentioned flexibility and the above-mentioned shape restoring property. The method of adjusting the yield strain Y2 includes, for example, selecting the type of components constituting the pressure-sensitive adhesive sheet 10 and adjusting the blending amount.

[0029] The adhesive sheet 10 has a strain stress S1 after the first third tensile test under conditions of 23° C., a tensile speed of 20 cm / min, and an elongation length of 150%, and has a strain stress S 10The third tensile test method and stresses S1, S 10 The method for measuring the stress S after repeated deformation is specifically described below in the Examples. 10 The ratio (S 10 The ratio (S / S1) in the adhesive sheet 10 is an index of the elastic recovery of the shape of the adhesive sheet after repeated deformation. 10 From the viewpoint of ensuring the above-mentioned elastic recovery of the pressure-sensitive adhesive sheet 10, the ratio (S 10 From the viewpoint of ensuring the flexibility of the pressure-sensitive adhesive sheet 10, the ratio (S 10 From the viewpoint of ensuring both the elastic recovery property and flexibility of the pressure-sensitive adhesive sheet 10, / S1) is preferably 0.5 to 1.2, more preferably 0.6 to 1.0, and even more preferably 0.65 to 0.95.

[0030] From the viewpoint of ensuring the above-mentioned elastic recovery of the adhesive sheet 10, the stress S1 of the adhesive sheet 10 is preferably 0.100 MPa or more, more preferably 0.120 MPa or more, and even more preferably 0.150 MPa or more. From the viewpoint of ensuring the stress relaxation property required for flexible device applications in the adhesive sheet 10, the stress S1 of the adhesive sheet 10 is preferably 0.215 MPa or less, more preferably 0.210 MPa or less, and even more preferably 0.205 MPa or less. That is, from the viewpoint of achieving both the above-mentioned elastic recovery property and stress relaxation property of the adhesive sheet 10, the stress S1 of the adhesive sheet 10 is preferably 0.100 to 0.215 MPa, more preferably 0.120 to 0.210 MPa, and even more preferably 0.150 to 0.205 MPa. Methods for adjusting the stress S1 of the adhesive sheet 10 include, for example, adjusting the monomer composition, molecular weight, and amount of blending of the base polymer in the adhesive sheet 10, and adjusting the degree of crosslinking (stress S 10 The same applies to .

[0031] Stress S of the adhesive sheet 10 10 From the viewpoint of ensuring the elastic recovery of the pressure-sensitive adhesive sheet 10 after repeated deformation, the stress S of the pressure-sensitive adhesive sheet 10 is preferably 0.070 MPa or more, more preferably 0.080 MPa or more, and even more preferably 0.090 MPa or more. 10 From the viewpoint of ensuring the stress relaxation property of the pressure-sensitive adhesive sheet 10 after repeated deformation, the stress S of the pressure-sensitive adhesive sheet 10 is preferably 0.215 MPa or less, more preferably 0.210 MPa or less, and even more preferably 0.205 MPa or less. 10 From the viewpoint of achieving both elastic recovery properties and stress relaxation properties of pressure-sensitive adhesive sheet 10 after repeated deformation, the compressive strength is preferably 0.070 to 0.215 MPa, more preferably 0.080 to 0.210 MPa, and even more preferably 0.090 to 0.205 MPa.

[0032] The pressure-sensitive adhesive sheet 10 is a sheet-like pressure-sensitive adhesive formed from a pressure-sensitive adhesive composition. The pressure-sensitive adhesive sheet 10 (pressure-sensitive adhesive composition) contains a base polymer. The base polymer is preferably a polymer (photopolymerized polymer) obtained by photopolymerization of a polymerizable component such as a monomer component. Photopolymerization is a polymerization method in which a polymerization reaction of a polymerizable component is advanced by irradiation with active energy rays such as ultraviolet rays.

[0033] Examples of the base polymer include acrylic polymer, polyurethane polymer, polyamide polymer, and polyvinyl ether polymer. The base polymer may be used alone or in combination of two or more. From the viewpoint of ensuring good adhesion and transparency in the adhesive sheet 10, the base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer of monomer components containing 50% or more by mass of (meth)acrylic acid ester. "(Meth)acrylic" means acrylic and / or methacrylic.

[0034] In this embodiment, the acrylic polymer is a polymerized product obtained by photopolymerization of a polymerizable component including a monofunctional monomer and a polyfunctional polymerizable compound as a crosslinking agent. The acrylic polymer is, for example, a polymerized product obtained by photopolymerization of a partial polymerized product (a mixture of a polymerized product of a monofunctional monomer and an unreacted monofunctional monomer) of a monofunctional monomer and a polyfunctional polymerizable compound.

[0035] Such an acrylic polymer includes a photopolymerized polymer (first photopolymerized polymer) having a photocrosslinked structure. The photocrosslinked structure is a structure in which a linear structure of units derived from a monofunctional monomer is crosslinked by a unit derived from a crosslinking agent. The base polymer may include a photopolymerized polymer (second photopolymerized polymer) that does not have such a photocrosslinked structure. The second photopolymerized polymer is a polymer of a monofunctional monomer.

[0036] The monofunctional monomer preferably contains a monofunctional (meth)acrylic acid alkyl ester, and more preferably contains a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 20 carbon atoms. The (meth)acrylic acid alkyl ester may have a linear or branched alkyl group, or may have a cyclic alkyl group (alicyclic alkyl group).

[0037] Examples of (meth)acrylic acid alkyl esters having a linear or branched alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, Examples of such acrylates include nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (i.e., (meth)acrylic laurate), isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, and nonadecyl (meth)acrylate.

[0038] Examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl ester, (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring, and (meth)acrylic acid alkyl ester having a tricyclic or higher aliphatic hydrocarbon ring. Examples of the (meth)acrylic acid cycloalkyl ester include (meth)acrylic acid cyclopentyl, (meth)acrylic acid cyclohexyl, (meth)acrylic acid cycloheptyl, and (meth)acrylic acid cyclooctyl. Examples of the (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring include (meth)acrylic acid isobornyl. Examples of (meth)acrylic acid alkyl esters having three or more aliphatic hydrocarbon rings include dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.

[0039] The monofunctional (meth)acrylic acid alkyl ester may be used alone or in combination of two or more kinds. The monofunctional (meth)acrylic acid alkyl ester is preferably an acrylic acid alkyl ester having an alkyl group having 3 to 12 carbon atoms, and more preferably at least one selected from the group consisting of n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), acrylate laurate (LA), and cyclohexyl acrylate (CHA).

[0040] The ratio of the (meth)acrylic acid alkyl ester in the monofunctional monomer is preferably 68 to 99% by mass, more preferably 70 to 85% by mass, and even more preferably 72 to 78% by mass. The ratio of the (meth)acrylic acid alkyl ester in the monofunctional monomer is preferably 68% by mass or more, more preferably 70% by mass or more, and even more preferably 72% by mass or more. When the ratio of the (meth)acrylic acid alkyl ester is equal to or more than the above lower limit, the adhesive sheet 10 can appropriately exhibit basic properties such as adhesiveness. In addition, the ratio of the monofunctional (meth)acrylic acid alkyl ester in the monofunctional monomer is preferably 99% by mass or less, more preferably 85% by mass or less, and even more preferably 78% by mass or less. When the ratio of the (meth)acrylic acid alkyl ester is equal to or less than the above upper limit, the ratio of the polar group-containing monomer in the base polymer described below can be ensured.

[0041] The monofunctional monomer may include a copolymerizable monomer that is copolymerizable with the (meth)acrylic acid alkyl ester. Examples of the copolymerizable monomer include a polar group-containing monomer. Examples of the polar group-containing monomer include a hydroxyl group-containing monomer, a monomer having a nitrogen atom-containing ring, and a carboxyl group-containing monomer. The copolymerizable monomer may be used alone or in combination of two or more kinds. The polar group-containing monomer is useful for modifying the acrylic polymer, such as ensuring the cohesive force of the acrylic polymer. The polar group-containing monomer is preferably at least one selected from the group consisting of a hydroxyl group-containing monomer and a monomer having a nitrogen atom-containing ring.

[0042] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA).

[0043] The ratio of the hydroxyl group-containing monomer in the monofunctional monomer is preferably 1 to 30% by mass, more preferably 5 to 28% by mass, and even more preferably 8 to 25% by mass. The ratio of the hydroxyl group-containing monomer in the monofunctional monomer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more. When the ratio of the hydroxyl group-containing monomer is equal to or more than the above lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 can be ensured, and the adhesive force of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured. In addition, the ratio of the hydroxyl group-containing monomer in the monomer component is preferably 30% by mass or less, more preferably 28% by mass or less, and even more preferably 25% by mass or less. When the ratio of the hydroxyl group-containing monomer is equal to or less than the above upper limit, the polarity of the acrylic polymer (related to the compatibility of the acrylic polymer with various additive components in the pressure-sensitive adhesive sheet 10) can be appropriately adjusted.

[0044] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen atom-containing ring is preferably N-vinyl-2-pyrrolidone (NVP).

[0045] The ratio of the monomer having a nitrogen atom-containing ring in the monofunctional monomer is preferably 1 to 30% by mass, more preferably 5 to 25% by mass, and even more preferably 10 to 20% by mass. The ratio of the monomer having a nitrogen atom-containing ring in the monofunctional monomer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. When the ratio of the monomer having a nitrogen atom-containing ring is equal to or more than the above lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 can be ensured, and the adhesive force of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured. In addition, the ratio of the monomer having a nitrogen atom-containing ring in the monofunctional monomer is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. When the ratio of the monomer having a nitrogen atom-containing ring is equal to or less than the above upper limit, the glass transition temperature of the acrylic polymer can be appropriately adjusted, and the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet 10 with the acrylic polymer) can be appropriately adjusted.

[0046] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0047] From the viewpoint of suppressing acid corrosion on the adherend of the pressure-sensitive adhesive sheet 10, the proportion of the carboxyl group-containing monomer in the monofunctional monomer is preferably 0 to 3 mass %, more preferably 0 to 1 mass %, even more preferably 0 to 0.5 mass %, even more preferably 0 to 0.1 mass %, and particularly preferably 0.0 mass %.

[0048] The monofunctional monomer may contain other copolymerizable monomers, such as acid anhydride monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, epoxy group-containing monomers, cyano group-containing monomers, alkoxy group-containing monomers, and aromatic vinyl compounds.

[0049] Examples of the polyfunctional polymerizable compound (crosslinking agent) include polyfunctional monomers containing two or more ethylenically unsaturated double bonds in one molecule. Examples of the polyfunctional monomers include polyfunctional (meth)acrylates. Examples of the polyfunctional (meth)acrylates include bifunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional or higher polyfunctional (meth)acrylates.

[0050] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, neopentyl glycol di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, dicyclopentenyl diacrylate, di(meth)acryloyl isocyanurate, and ethoxylated bisphenol A diacrylate (BPAEODE).

[0051] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.

[0052] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.

[0053] The multifunctional polymerizable compound may be used alone or in combination of two or more kinds. The multifunctional polymerizable compound is preferably at least one selected from the group consisting of 1,6-hexanediol diacrylate (HDDA) and dipentaerythritol hexaacrylate (DPHA).

[0054] The amount of the polyfunctional polymerizable compound in the polymerizable component is preferably 0.01 to 2 parts by mass, more preferably 0.05 to 1.5 parts by mass, and even more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the monofunctional monomer. The amount of the polyfunctional polymerizable compound in the polymerizable component is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the monofunctional monomer. When the amount of the polyfunctional polymerizable compound is equal to or more than the above lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 is increased, and the adhesive reliability after being attached to the adherend is improved. The amount of the polyfunctional polymerizable compound in the polymerizable component is preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1 part by mass or less, relative to 100 parts by mass of the monofunctional monomer. When the amount of the polyfunctional polymerizable compound is equal to or less than the above upper limit, the flexibility of the pressure-sensitive adhesive sheet 10 is easily ensured.

[0055] In this embodiment, the acrylic polymer is formed by photopolymerization of the polymerizable components. The polymerizable components (including a monofunctional monomer and a polyfunctional polymerizable compound as a crosslinking agent) may be polymerized in one step or in multiple steps. In the multistep polymerization method, a prepolymer composition containing a partial polymer (a mixture of a polymer of a monofunctional monomer and an unreacted monofunctional monomer) is first prepared by polymerizing a monofunctional monomer (preliminary polymerization). Next, a polyfunctional polymerizable compound as a crosslinking agent is added to the prepolymer composition, and then a polymerization reaction is allowed to proceed in a reaction system containing the partial polymer and the polyfunctional polymerizable compound (main polymerization). In the photopolymerization, a photopolymerization initiator may be used.

[0056] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.

[0057] Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, and an α-ketol photopolymerization initiator.

[0058] Examples of the acylphosphine oxide photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethan-1-one. Examples of the acetophenone photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. The photopolymerization initiator may be used alone or in combination of two or more. The photopolymerization initiator is preferably at least one selected from the group consisting of 2,2-dimethoxy-1,2-diphenylethan-1-one and 1-hydroxycyclohexyl phenyl ketone.

[0059] The amount of the photopolymerization initiator is preferably 0.03 to 0.5 parts by mass, more preferably 0.06 to 0.3 parts by mass, and even more preferably 0.08 to 0.2 parts by mass, relative to 100 parts by mass of the polymerizable component. The amount of the photopolymerization initiator is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, and even more preferably 0.08 parts by mass or more, relative to 100 parts by mass of the polymerizable component. When the amount of the photopolymerization initiator is equal to or more than the above lower limit, a crosslinked network with sufficient crosslinking density is formed in the acrylic polymer, and the adhesive strength of the adhesive sheet 10 can be ensured. The amount of the photopolymerization initiator is preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, and even more preferably 0.2 parts by mass or less, relative to 100 parts by mass of the polymerizable component. When the amount of the photopolymerization initiator is equal to or less than the above upper limit, cohesive failure of the adhesive surface of the adhesive sheet 10 can be suppressed when the adhesive sheet 10 is peeled off from the adherend. When the acrylic polymer is photopolymerized by preliminary polymerization and main polymerization, a photopolymerization initiator may be added after the preliminary polymerization and during the main polymerization.

[0060] From the viewpoint of ensuring the cohesive force of the adhesive sheet 10, the weight average molecular weight of the base polymer is preferably 100,000 to 5,000,000, more preferably 300,000 to 3,000,000, and even more preferably 500,000 to 2,000,000. The weight average molecular weight of the base polymer is preferably 100,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more. When the weight average molecular weight of the base polymer is equal to or more than the above lower limit, the cohesive force of the adhesive sheet 10 can be ensured. The weight average molecular weight of the base polymer is preferably 5,000,000 or less, more preferably 3,000,000 or less, and even more preferably 2,000,000 or less. When the weight average molecular weight of the base polymer is equal to or less than the above upper limit, the flexibility of the adhesive sheet 10 can be ensured. The weight average molecular weight of the acrylic polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.

[0061] From the viewpoint of ensuring the flexibility of the base polymer, the glass transition temperature (Tg) of the base polymer is preferably 0° C. or lower, more preferably -10° C. or lower, and even more preferably -20° C. or lower. The glass transition temperature is, for example, -80° C. or higher. That is, the glass transition temperature of the base polymer is preferably -80° C. to 0° C., more preferably -80° C. to -10° C., and even more preferably -80° C. to -20° C.

[0062] The glass transition temperature of the base polymer may be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of a polymer, Wi represents the weight fraction of a monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of a homopolymer may be determined by a literature value. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999). On the other hand, the glass transition temperature of a homopolymer of a monomer may be determined by a method specifically described in JP-A-2007-51271.

[0063] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]

[0064] The content of the base polymer in the adhesive sheet 10 is preferably 80 to 99.9% by mass, more preferably 85 to 99.5% by mass, and even more preferably 90 to 99.0% by mass. The content of the base polymer in the adhesive sheet 10 is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more. When the content of the base polymer is equal to or more than the above lower limit, basic properties such as adhesiveness can be appropriately exhibited in the adhesive sheet 10. The content of the base polymer in the adhesive sheet 10 is, for example, 99.9% by mass or less, 99.5% by mass or less, or 99.0% by mass or less.

[0065] The pressure-sensitive adhesive sheet 10 may contain other components, such as an oligomer, a silane coupling agent, an ultraviolet absorbing agent, an antioxidant, a surfactant, and a rust inhibitor.

[0066] The release liner 20 has a release surface 21 on the side facing the adhesive sheet 10. The release liner 20 is in releasable contact with the adhesive surface 11 of the adhesive sheet 10 on the release surface 21 side. In this embodiment, the release liner 20 is a heavy release liner that requires a greater force to be peeled off from the adhesive sheet 10 than the release liner 30.

[0067] Examples of the release liner 20 include a release liner in which a release surface 21 is formed on a liner substrate by a release treatment layer, and a release liner formed from a low-adhesion material. Examples of the liner substrate include a resin film and paper. Examples of the resin of the resin film include a polyester resin and a polycarbonate resin. Examples of the polyester resin include polyethylene terephthalate (PET) and polybutylene terephthalate. The release treatment layer can be formed by surface treating the liner substrate with a release treatment agent. Examples of the release treatment agent include a silicone release treatment agent, a long-chain alkyl release treatment agent, and a fluorine release treatment agent. Examples of the low-adhesion material include a polyolefin resin and a fluorine-based polymer. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the fluorine-based polymer include polytetrafluoroethylene.

[0068] The maximum height Sz of the release surface 21 is preferably 2000 nm or less, more preferably 1800 nm or less, and even more preferably 1700 nm or less, from the viewpoint of reducing the maximum height Sz of the adhesive surface 11 of the adhesive sheet 10. The maximum height Sz of the release surface 21 is preferably 1000 nm or more, more preferably 1200 nm or more, and even more preferably 1300 nm or more, from the viewpoint of suppressing unintended peeling of the release liner 20 from the adhesive sheet 10. The maximum height Sz of the release surface 21 is preferably 1000 to 2000 nm, more preferably 1200 to 1800 nm, and even more preferably 1300 to 1700 nm, from the viewpoint of both reducing the maximum height Sz of the adhesive surface 11 and suppressing the above-mentioned peeling of the release liner 20. Examples of methods for adjusting the maximum height Sz of the release surface 21 include adjusting the surface roughness of the coating film when a release treatment agent is applied to the liner substrate described below (the same applies to the maximum height Sz of the release surface 31 of the release liner 30).

[0069] The release liner 30 has a release surface 31 on the side facing the adhesive sheet 10. The release liner 30 is in releasable contact with the adhesive surface 12 of the adhesive sheet 10 on the release surface 31 side. In this embodiment, the release liner 30 is a light release liner that requires less force to be peeled off from the adhesive sheet 10 compared to the release liner 20.

[0070] Examples of the release liner 30 include a release liner having a release treatment layer on the surface of a liner substrate and a release liner formed from a low adhesion material. Specifically, the material of the release liner 30 is the same as the material described above for the release liner 20.

[0071] The maximum height Sz of the release surface 31 is preferably 2000 nm or less, more preferably 1800 nm or less, and even more preferably 1700 nm or less, from the viewpoint of reducing the maximum height Sz of the adhesive surface 12 of the adhesive sheet 10. The maximum height Sz of the release surface 31 is preferably 1000 nm or more, more preferably 1200 nm or more, and even more preferably 1300 nm or more, from the viewpoint of suppressing unintended peeling of the release liner 30 from the adhesive sheet 10. The maximum height Sz of the release surface 31 is preferably 1000 to 2000 nm, more preferably 1200 to 1800 nm, and even more preferably 1300 to 1700 nm, from the viewpoint of achieving both a reduction in the maximum height Sz of the adhesive surface 12 and the suppression of the above-mentioned peeling of the release liner 30.

[0072] The adhesive sheet 10 can be produced, for example, as follows.

[0073] First, a prepolymer composition is prepared. Specifically, a mixture (liquid) containing the monofunctional monomer for forming the base polymer and a photopolymerization initiator is prepared. Next, the mixture is irradiated with ultraviolet light to photopolymerize a portion of the monofunctional monomer in the mixture to obtain a prepolymer composition. Examples of light sources for ultraviolet light irradiation include ultraviolet LED lights, black light lamps, high-pressure mercury lamps, and metal halide lamps. In the ultraviolet light irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2The cumulative irradiation dose is, for example, 100 to 5000 mJ / cm 2 The ultraviolet irradiation is preferably continued until the viscosity of the composition reaches about 15 to 25 Pa·s. This viscosity is measured using a Brookfield viscometer with a No. 5 rotor at a rotor speed of 10 rpm and at a temperature of 30°C. The prepolymer composition contains a photopolymerized product of a monofunctional monomer and an unreacted monofunctional monomer (residual monomer). The prepolymer composition does not contain a solvent.

[0074] Next, a multifunctional polymerizable compound (crosslinking agent) and other components as necessary are added to the prepolymer composition to prepare a pressure-sensitive adhesive composition. The other components include, for example, an oligomer, an additional photopolymerization initiator, a silane coupling agent, an antioxidant, and a rust inhibitor. This pressure-sensitive adhesive composition does not contain a solvent. That is, the pressure-sensitive adhesive composition prepared in this process is a solventless pressure-sensitive adhesive composition.

[0075] Next, a pressure-sensitive adhesive composition is applied onto release surface 21 of release liner 20 to form a coating film, and then release surface 31 of release liner 30 is attached to the coating film on release liner 20. Examples of methods for applying the pressure-sensitive adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating.

[0076] Next, the coating film between the release liners 20 and 30 is irradiated with ultraviolet light to photo-cure the coating film, forming an adhesive layer (adhesive layer forming step). The ultraviolet light irradiation causes a polymerization reaction in the coating film in a reaction system containing the residual monomer and the polyfunctional polymerizable compound, forming a first photopolymerized polymer having a photocrosslinking structure. Thereafter, the adhesive layer may be dried by heating. The drying temperature is, for example, 80°C to 150°C. The drying time is, for example, 30 seconds to 10 minutes. The drying process allows the unreacted monomer in the adhesive layer to be volatilized and removed. The maximum height Sz of the release surfaces 21 and 31 being 2000 nm or less is suitable for forming an adhesive layer (adhesive sheet 10) between the release surfaces 21 and 31 with high smoothness of the adhesive surfaces 11 and 12.

[0077] In this manner, it is possible to produce an adhesive sheet 10 in which adhesive surfaces 11, 12 are covered and protected by release liners 20, 30. In other words, it is possible to produce an adhesive sheet X with a release liner. Release liners 20, 30 are peeled off from adhesive sheet 10 as necessary when adhesive sheet 10 is to be used.

[0078] The pressure-sensitive adhesive sheet 10 can be formed from a solvent-free pressure-sensitive adhesive composition. Such a pressure-sensitive adhesive sheet 10 is suitable for reducing the environmental load. That is, the pressure-sensitive adhesive sheet 10 formed from a solvent-free pressure-sensitive adhesive composition is environmentally friendly and preferable from the viewpoint of sustainable development.

[0079] The thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, from the viewpoint of ensuring sufficient adhesion to the adherend. The thickness of the pressure-sensitive adhesive sheet 10 is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less, from the viewpoint of ease of handling and thinning of the pressure-sensitive adhesive sheet 10. The thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 to 300 μm, more preferably 20 to 200 μm, and even more preferably 30 to 100 μm, from the viewpoint of achieving both the above-mentioned adhesion and the above-mentioned ease of handling and thinning.

[0080] The adhesive sheet 10 is, for example, an optical adhesive sheet arranged at a light passing portion in a flexible device. An example of a flexible device is a flexible display panel. An example of a flexible display panel is a foldable display panel, a rollable display panel, and a stretchable display panel. A flexible display panel is a display panel that can be repeatedly folded. A rollable display panel is a display panel that can be repeatedly rolled up. A stretchable display panel is a display panel that can be repeatedly deformed (stretched, twisted, folded, etc.). A flexible display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover film. The adhesive sheet 10 is used, for example, in the manufacturing process of a flexible display panel, to bond elements included in the laminated structure to each other. EXAMPLES

[0081] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".

[0082] <Preparation of the first heavy release liner> A first release agent solution with a silicone solids concentration of 1.25% by mass was prepared by mixing 80 parts by mass of a silicone release agent (product name "KE-3703", a 28.5% by mass toluene solution of an addition type silicone release agent containing a polyorganosiloxane having a hexenyl group in the molecule and a polyorganosiloxane crosslinker having a hydrosilyl group in the molecule, manufactured by Shin-Etsu Chemical Co., Ltd.), 20 parts by mass of a silicone release control agent (product name "KS-3800", manufactured by Shin-Etsu Chemical Co., Ltd.), 3.0 parts by mass of a platinum catalyst for silicone curing (product name "CAT-PL-50T", manufactured by Shin-Etsu Chemical Co., Ltd.), and a solvent. The solvent was a mixed solvent of toluene and hexane in a volume ratio of 1:1.

[0083] Next, a first polyethylene terephthalate (PET) film (thickness 75 μm, maximum surface height Sz 1480 nm) was subjected to a release treatment as a base film. Specifically, the above-mentioned first release treatment agent solution was applied to one side of the base film to form a coating film. A wire bar #9 was used for application. The amount of application was 0.1 g / m2 in terms of solid content. 2 Next, the coating film on the substrate film was dried by heating at 130° C. for 1 minute using a hot air dryer, thereby forming a silicone release layer on the substrate film.

[0084] In this manner, a first heavy release liner (substrate film / release layer) was produced. The maximum height Sz of the surface of the first heavy release liner on the release layer side was 1504 nm.

[0085] <Preparation of the second release liner> A second release liner (substrate film / release layer) was prepared in the same manner as the first release liner, except for the following: A second PET film (thickness 75 μm, maximum surface height Sz 3460 nm) was used as the substrate film. The maximum surface height Sz of the release layer side of the second release liner was 3320 nm.

[0086] <Preparation of the first light release liner> A second release treatment agent solution with a silicone solids concentration of 1.0 mass% was prepared by mixing 100 parts by mass of a silicone-based release treatment agent (product name "KS-847T", a 30% toluene solution of vinyl group-containing addition type silicone, manufactured by Shin-Etsu Chemical Co., Ltd.), 3.0 parts by mass of a platinum catalyst for silicone curing (product name "CAT-PL-50T", manufactured by Shin-Etsu Chemical Co., Ltd.), 15,000 parts by mass of toluene as a solvent, and 1,500 parts by mass of normal hexane.

[0087] Next, a first PET film (thickness 75 μm, maximum surface height Sz 1480 nm) was subjected to a release treatment as a base film. Specifically, the second release treatment agent solution was applied to one side of the base film to form a coating film. A wire bar #9 was used for application. The amount of application was 0.1 g / m2 in terms of solid content. 2 Next, the coating film on the substrate film was dried by heating at 130° C. for 1 minute using a hot air dryer, thereby forming a silicone release layer on the substrate film.

[0088] In this manner, a first light release liner (base film / release layer) was produced. The maximum height Sz of the surface of the first light release liner on the release layer side was 1680 nm.

[0089] <Preparation of the second light release liner> A second light release liner (substrate film / release layer) was produced in the same manner as the first light release liner, except that a second PET film (thickness 75 μm, maximum surface height Sz 3460 nm) was used as the substrate film. The maximum surface height Sz of the release layer side of the second light release liner was 3730 nm.

[0090] Example 1 Preparation of Pressure-Sensitive Adhesive Composition First, a mixture containing 75 parts by mass of 2-ethylhexyl acrylate (2EHA), 10 parts by mass of 2-hydroxyethyl acrylate (HEA), 15 parts by mass of N-vinyl-2-pyrrolidone (NVP), 0.05 parts by mass of a first photopolymerization initiator (product name "Omnirad 184", 1-hydroxycyclohexyl-phenyl-ketone, manufactured by BASF), and 0.05 parts by mass of a second photopolymerization initiator (product name "Omnirad 651", 2,2-dimethoxy-1,2-diphenylethan-1-one, manufactured by BASF) was irradiated with ultraviolet light (polymerization reaction) to obtain a prepolymer composition (polymerization rate of about 10%) (the prepolymer composition contains unreacted monomer components). Next, 100 parts by mass of the prepolymer composition and 0.3 parts by mass of 1,6-hexanediol diacrylate (HDDA) (product name "A-HD-N", manufactured by Shin-Nakamura Chemical Co., Ltd.) as a first crosslinking agent were mixed to obtain a first adhesive composition.

[0091] <Formation of Adhesive Layer> First, the first pressure-sensitive adhesive composition was applied onto the first heavy release liner to form a coating film. The coating film was formed on the silicone release layer of the first heavy release liner. Next, the silicone release layer side of the first light release liner was attached to the coating film on the first heavy release liner (attaching process). Next, the coating film was irradiated with ultraviolet light through the first light release liner to cure the coating film with ultraviolet light, forming a transparent first pressure-sensitive adhesive layer with a thickness of 100 μm. For ultraviolet irradiation, a black light was used as the irradiation light source, and the irradiation intensity was 5 mW / cm. 2 It was decided.

[0092] In this manner, the pressure-sensitive adhesive sheet with release liner of Example 1 (first heavy release liner / pressure-sensitive adhesive sheet (first pressure-sensitive adhesive layer) / second light release liner) was produced.

[0093] [Example 2, Comparative Examples 1 to 3] The adhesive sheets with release liner of each of the examples and comparative examples were prepared in the same manner as the adhesive sheet with release liner of Example 1, except that the monomer composition of the base polymer and the formulation of the crosslinking agent were changed as shown in Table 1, and the release liner shown in Table 1 was used.

[0094] <Maximum height Sz> The maximum heights Sz of the first adhesive surface and the second adhesive surface of each of the adhesive sheets with release liners in the Examples and Comparative Examples were examined. The first adhesive surface is the adhesive surface that contacts the heavy release liner. The second adhesive surface is the adhesive surface that contacts the light release liner.

[0095] Specifically, first, a piece of adhesive sheet with a release liner was cut out of a predetermined size from the adhesive sheet with a release liner. Next, the light release liner was peeled off from the adhesive sheet of the sheet piece, and the adhesive surface (second adhesive surface) exposed thereby was attached to a slide glass (manufactured by Matsunami Glass Co., Ltd.). Then, the heavy release liner was peeled off from the adhesive sheet on the slide glass, and the adhesive surface (first adhesive surface) exposed thereby was observed and photographed with a three-dimensional optical interference optical microscope (product name "ContourX-200", manufactured by Bruker) (first observation). In the observation, the measurement type was set to USI mode, and a 10x objective lens and a 0.55x internal lens were used, and the maximum height Sz was obtained from the observation image with a measurement area of ​​1.3 mm x 1.5 mm (the maximum height Sz is the sum of the maximum peak height Sp and the maximum valley depth Sv. These are parameters based on ISO 25178-2:2012). The maximum height Sz was also measured under the same conditions for the second adhesive surface of another piece of adhesive sheet cut out from the same adhesive sheet with release liner. The larger of the maximum heights Sz measured for the first and second adhesive surfaces is shown in Table 1 as the maximum height Sz (nm) of the adhesive surface.

[0096] Meanwhile, the maximum height Sz of the surface on the silicone release layer side was examined for each of the first heavy release liner, the second heavy release liner, the first light release liner, and the second light release liner. Specifically, first, the release layer surface of the release liner was observed and photographed using the optical microscope described above (second observation). The conditions for the second observation were the same as those for the first observation described above. Next, the maximum height Sz (nm) was calculated from the observed image (measurement area 1.3 mm × 1.5 mm). The results are shown in Table 1.

[0097] Haze For each of the pressure-sensitive adhesive sheets of the Examples and Comparative Examples, the haze H0 when unstretched was measured as follows.

[0098] First, a sample for haze measurement was prepared. Specifically, first, a piece of adhesive sheet with release liner (width 5 mm x length 5 mm) was cut out from an adhesive sheet with release liner. Next, the light release liner was peeled off from the adhesive sheet of the sheet piece. Next, the exposed surface of the adhesive sheet was attached to a slide glass (manufactured by Matsunami Glass Co., Ltd.). Next, the heavy release liner was peeled off from the adhesive sheet on the slide glass. This resulted in a sample for haze measurement.

[0099] Next, the haze of the samples was measured in accordance with JIS K7136:2000 using a haze meter "HM-150" manufactured by Murakami Color Research Laboratory Co., Ltd. In addition, in this measurement, the measurement results obtained by measuring only the slide glass under the same conditions were used as the baseline. The haze (%) of each pressure-sensitive adhesive sheet is shown in Table 1 as the haze H0 when not stretched.

[0100] On the other hand, for each of the pressure-sensitive adhesive sheets of the Examples and Comparative Examples, the haze H0 at 150% elongation was measured in the same manner as in the measurement of haze H0, except for the following: 150 In preparing a sample for haze measurement, both release liners were peeled off from a piece of adhesive sheet with release liner (width 5 mm × length 5 mm), and the adhesive sheet was stretched in the length direction to 150% and then attached to a glass slide.

[0101] The measurement results are shown in Haze H at 150% elongation. 150 The haze H is shown in Table 1. 150 The absolute value of the difference between the haze H0 and the haze H0 is ΔH (= |H 150 The values ​​of -H0| are also shown in Table 1.

[0102] Tensile Test The pressure-sensitive adhesive sheets of the Examples and Comparative Examples were subjected to the following first tensile test.

[0103] Specifically, first, the required number of test pieces were prepared for each adhesive sheet. In preparing the test pieces, first, an adhesive sheet piece with a release liner (width 40 mm x length 40 mm) was cut out from an adhesive sheet with a release liner. Next, one release liner was peeled off from the sheet piece, and then the adhesive sheet piece was rolled up in the length direction on the other release liner while being careful not to trap air bubbles, to form a cylindrical shape (cylinder height 40 mm). In this way, a cylindrical adhesive sheet piece was obtained as a test piece.

[0104] Next, a tensile test was performed on the test piece using a Tensilon type tensile tester (product name "Autograph AG-50NX plus", manufactured by Shimadzu Corporation) in an environment of 23°C and relative humidity of 50% (first tensile test). In this tensile test, the initial chuck distance was 10 mm, the tensile speed was 10 mm / min, and the test piece (cylindrical adhesive sheet piece) was pulled in the height direction of the cylindrical shape until it broke. The strain at the time of breakage (yield point) of the test piece in the first tensile test is shown in Table 1 as yield strain Y1 (%). The yield strain is the ratio (ΔL / L0) of the elongation length ΔL of the test piece at the time the test piece breaks to the initial length L0 of the test piece in the tensile direction in the tensile test. The elongation length ΔL is the amount of elongation from the initial length L0 of the test piece.

[0105] A second tensile test was also carried out on another test piece of each pressure-sensitive adhesive sheet of the Examples and Comparative Examples. The second tensile test was the same as the first tensile test, except that the tensile speed was changed from 10 mm / min to 1500 mm / min. The strain at the break of the test piece in the second tensile test is shown in Table 1 as the yield strain Y2 (%).

[0106] Meanwhile, for other test pieces of each pressure-sensitive adhesive sheet of the Examples and Comparative Examples, one cycle in which the following steps 1 to 3 are performed in sequence was repeated 10 times while measuring the stress generated in the test piece, and the stress retention was examined. The stress at the end of step 1 of the first cycle is shown in Table 1 as stress S1. The stress at the end of step 2 of the tenth cycle is shown in Table 1 as stress S 10 The stress S1 is shown in Table 1. 10 The ratio (S 10 / S1) are also shown in Table 1.

[0107] Step 1: The test piece was pulled to an elongation length of 150% using a tensile tester (Autograph AG-50NX plus) in an environment of 23°C and relative humidity of 50% (third tensile test). In this tensile test, the initial chuck distance was 10 mm, the pulling speed was 20 cm / min, and the test piece (cylindrical adhesive sheet piece) was pulled in the height direction of the cylinder.

[0108] Step 2: The test specimen was held at 150% of its elongation for 300 seconds.

[0109] Step 3: The test piece was returned to its original length (0% elongation).

[0110] The adhesive sheets of Comparative Examples 1 to 3 each had a maximum height Sz of the adhesive surface that was significantly greater than 500 nm. In such adhesive sheets, surface irregularities on the adhesive surface become greater when the adhesive sheet is stretched. Such adhesive sheets are not suitable for flexible device applications. The adhesive sheet of Comparative Example 3 had a haze H 150 The difference between the haze H0 when stretched and the ratio (S 10 / S1) was less than 60%, and the stress retention was low. Such an adhesive sheet is also not suitable for flexible device applications.

[0111] In contrast, the adhesive sheets of the Examples had a maximum adhesive surface height Sz of 500 nm or less, and the above-mentioned haze difference ΔH was 1.0%. Such adhesive sheets are suitable for use in flexible devices to suppress the occurrence of large surface irregularity defects and to suppress an increase in haze. In addition, the adhesive sheets of the Examples had a ratio (S 10 / S1) significantly exceeded 60%, and the stress retention was high.

[0112] [Table 1] [Explanation of symbols]

[0113] X Adhesive sheet with release liner H Thickness direction 10 Adhesive sheet 11 Adhesive surface (1st adhesive surface) 12 Adhesive surface (second adhesive surface) 20 Release liner (first release liner) 21 Peeling surface 30 Release liner (secondary release liner) 31 Peeling surface

Claims

1. An optical adhesive sheet having a first adhesive surface and a second adhesive surface opposite to the first adhesive surface, The maximum height Sz of the first adhesive surface and the second adhesive surface is 500 nm or less, Haze at 150% elongation 150 (%) and haze H when not stretched 0 (%)but, |H 150 -H 0 An optical adhesive sheet that satisfies |≦1.

0.

2. The Haze H 0 The optical adhesive sheet according to claim 1 , wherein the optical adhesive sheet has a refractive index of 2.0% or less.

3. Yield strain Y in the first tensile test at 23°C and a tensile speed of 10 mm / min 1 The optical pressure-sensitive adhesive sheet according to claim 1 , wherein the optical coefficient of curvature is 150% or more.

4. Yield strain Y in the second tensile test at 23°C and a tensile speed of 1500 mm / min 2 The optical pressure-sensitive adhesive sheet according to claim 1 , wherein the optical coefficient of curvature is 150% or more.

5. After the first third tensile test under the conditions of 23° C., tensile speed 20 cm / min and elongation length 150%, the strain stress S 1 and after the tenth third tensile test, the strain stress S 10 and the stress S 1 The stress S 10 The optical adhesive sheet according to claim 1 , wherein the ratio is 0.5 or more.

6. The optical adhesive sheet according to any one of claims 1 to 5, a first release liner releasably contacting the first adhesive surface; An optical adhesive sheet with a release liner, comprising a second release liner releasably contacting the second adhesive surface.

7. The maximum height Sz of the surface of the first release liner on the optical adhesive sheet side is 2000 nm or less; The optical adhesive sheet with a release liner according to claim 6 , wherein the maximum height Sz of the surface of the second release liner on the optical adhesive sheet side is 2000 nm or less.

Citation Information

Patent Citations

  • Adhesive sheet

    JP2018111754A